Organoleptic Attributes and Proximate Composition of Bean Ball (Akara) Produced from Composite Flour of Selected Legumes - A.E, Achebe; E. U., Anyakoha (Journal of Home Economics Research, 2024)
This study evaluated the organoleptic attributes and proximate composition of bean ball (akara) produced from composite flour of cowpea (Vigna unguiculata) soybean (Glycine max), and bambara nut (Voandzeia subterrana). There were six ratios. Proximate analysis was carried out (moisture, ash, fat, protein, fibre and carbohydrates) using standard methods. Organoleptic attributes were ascertained using a 9-point hedonic rating scale by panel of 30 assessors. Data were analysed using mean and standard deviation and ANOVA. Proximate analysis showed that composite flour increased in protein content from 23.21 to 30.51% fiber1.37 to 1,38 fat 2.31 to 4.65%. ANOVA results indicate no significant difference in all the ratings of bean balls produced with composite of six different ratios at 0.05 level of significance, based on the organoleptic attributes.